A rare case of hemangiopericytoma with anterior chest wall involvement and scalp metastasis [Göǧüs ön duvari tutulumu ve skalp metastazi ile seyreden nadir bir hemanjiyoperistom olgusu] - (:unkn) unknown (My University, 2011)
Hemangiopericytoma is described as a distinct entity of vascular tumor which originates from the contractile pericytes of Zimmermann around capillaries and venules. These rare mesenchymal tumors may develop at almost any age, but usually they occur during the fifth or seventh decade. In adults, the common sites of origin are in the lower extremity and retroperitoneum, whereas in children the tumors have a predilection for the head and neck region and lower extremities. It usually demonstrates a slow progression in size with high local recurrence rate following surgical intervention. A rare case of hemangiopericytoma in a 18-year-old male patient is presented, who was first diagnosed with hemangiopericytoma involving anterior chest wall and underwent later on further surgical operations owing to the emergence of local recurrence and metastasis to his vertebra and scalp.
Keywords: Anterior chestwall; Hemangiopericytoma; Metastasis; Scalp